2006
DOI: 10.1074/jbc.m509121200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Inhibition of mRNA Degradation Pathways by Novel Cap Analogs

Abstract: mRNA degradation predominantly proceeds through two alternative routes: the 533 pathway, which requires deadenylation followed by decapping and 533 hydrolysis; and the 335 pathway, which involves deadenylation followed by 335 hydrolysis and finally decapping. The mechanisms and relative contributions of each pathway are not fully understood. We investigated the effects of different cap structure (Gp 3 G, m 7 Gp 3 G, or m 2 7,3-O Gp 3 G) and 3 termini (A 31 , A 60 , or G 16 ) on both translation and mRNA degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
113
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(120 citation statements)
references
References 75 publications
6
113
0
1
Order By: Relevance
“…This assumption is based on the finding that protection of the 5 0 end of an RNA against cleavage by Dcp2 shifts the balance of 5 0 -3 0 and 3 0 -5 0 degradation to the latter. 25 In a recent report that is consistent with our data, it was shown that ectopic CD40L expression in immature DCs is higher from post-transcriptionally capped RNA compared with ARCA-capped RNA. 26 However, b-S-ARCA(D1) (or D2) was not tested by these investigators, and thus the superiority of b-S-ARCA(D1)-capped RNAs over post-transcriptionally capped RNA on protein expression and RNA stability in immature DCs remained unrevealed.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This assumption is based on the finding that protection of the 5 0 end of an RNA against cleavage by Dcp2 shifts the balance of 5 0 -3 0 and 3 0 -5 0 degradation to the latter. 25 In a recent report that is consistent with our data, it was shown that ectopic CD40L expression in immature DCs is higher from post-transcriptionally capped RNA compared with ARCA-capped RNA. 26 However, b-S-ARCA(D1) (or D2) was not tested by these investigators, and thus the superiority of b-S-ARCA(D1)-capped RNAs over post-transcriptionally capped RNA on protein expression and RNA stability in immature DCs remained unrevealed.…”
Section: Discussionsupporting
confidence: 81%
“…The stabilization of b-S-ARCA(D1)-capped RNA would thus be explained by efficient binding of eIF4E to the 5 0 end, as previously shown. 25 In contrast, in mature DCs the influence of RNA stabilization and affinity for eIF4E seems to be the opposite, because b-S-ARCA(D2)-capped RNA gives highest protein synthesis. In addition, our data can be observed as an indication for domination of 5 0 -3 0 rather than 3 0 -5 0 degradation routes in immature DCs.…”
Section: Discussionmentioning
confidence: 99%
“…Stabilities were predicted using Mfold version 3.0 (60). RNA was synthesized by transcribing plasmids with T7 RNA polymerase (61). Capped mRNAs were produced by lowering the GTP concentration from 0.5 to 0.1 mM and including the ARCA at 1 mM (62), which prevents the cap from being incorporated in the reverse orientation (51).…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of the SB reporter RNA lacking a 5Ј cap structure was completed by using a Ribomax (Qiagen) RNA probe kit. Reporter RNAs synthesized with host decapping enzyme cleavage-resistant cap analog were transcribed as described previously (19). For radiolabeling of in vitro-transcribed RNA, transcripts were synthesized as described above in the presence of [ 32 P] ATP (Amersham), precipitated as described above, and used directly for electroporation.…”
Section: Methodsmentioning
confidence: 99%
“…This result suggested that an IFN-␣/␤-induced decapping activity might account for the translation inhibition observed. To test this, we electroporated IFN-␣/␤-treated and untreated cells with transcripts produced using a cap structure (m 27,3Ј-O Gpp CH2 pG) that has been shown to be highly resistant to the Dcp2 decapping enzyme in vitro and to significantly retard RNA degradation in cells (19). The effects of IFN-␣/␤ priming on translation were similar in magnitude if the cleavage-resistant cap was used for transcription (Fig.…”
Section: Translation Of Sb and Other Cap-dependent Virus Mrnas Is Inhmentioning
confidence: 99%